Iš viešojo administravimo praeities Lietuvoje: 1940 m. Politikos ir socialinių mokslų instituto Administravimo kursai - Raipa, Alvydas; Smalskys, Vainius (Lietuvos istorijos studijos, 2001)
In 1940 January-February in Lithuania was established Political and Social Sciences Institute's Courses of administration. It was purposed to improve public staff works effectiveness and ready to help administration reforms in Lithuania. Rulers of these Courses in duties of Rectors invited famous scientists, state and society leaders, because they wanted to raise public staff training quality. In programs of Courses of administration, in majority was law aspects of training, but not management aspect. However, a wide management program "Organizations of administration" was included.